SENSORY QUALITY ANALYSIS OF FETTUCINE PASTA WITH MORINGA LEAF EXTRACT SUBSTITUTION - zahwa devilia; Rahmi Holinesti; Wiwik Gusnita; Riski Gusri Utami (Department of Food Technology, Universitas Pasundan, Bandung, 2026)
Fettuccine pasta is a widely consumed food product due to its distinctive flavor and high carbohydrate content. However, pasta products generally have relatively low levels of vitamins, minerals, and antioxidants, necessitating innovation through the use of highly nutritious local ingredients. One potential ingredient is Moringa oleifera (moringa) leaf extract, which is rich in vitamins, minerals, protein, and antioxidant compounds. This study aimed to analyze the effect of substituting moringa leaf extract on the sensory quality of fettuccine pasta, specifically regarding shape, color, aroma, taste, texture, and overall acceptability. An experimental method was employed using a Completely Randomized Design (CRD) with a single factor—the concentration of moringa leaf extract substitution—comprising two treatments replicated three times. Sensory quality was assessed via organoleptic testing with 30 untrained panelists, and data were analyzed using an independent sample t-test. The results indicated that the substitution of moringa leaf extract significantly influenced the shape, color, aroma, taste, texture, and overall acceptability of the fettuccine pasta. Higher concentrations of moringa leaf extract resulted in a more intense green color; however, at certain concentrations, the aroma, taste, texture, and level of acceptability remained acceptable to the panelists. Based on the findings, the formulation with the optimal concentration of moringa leaf extract produced fettuccine pasta with favorable sensory characteristics, showing potential for development as a more nutritious functional food product that is competitive as a natural-ingredient-based food innovation.